Bio-inspired synthesis of nanomaterials for metal-ion batteries - Mah, Theodosius Yong Jian (2018)
There exists in nature many interesting biological substances which are of great interest as templates for nanomaterial synthesis. This is because these biological substances can provide an environmentally friendly and low cost alternative for nanomaterial synthesis. Nanomaterials synthesised as such also possess better electrochemical properties as compared to nanomaterials prepared with the traditional method. This allows nanomaterials prepared through bio-inspired synthesis methods to have potential applcations in batteries. There however is a challenge in tuning the shape and size of nanomaterials synthesised with bio-templates. In this study, attempts were made to synthesise hollow Fe2O3 nanoparticles for use in battery anode applications as proposed by Yan and Fong (2017). Attempts were also made to optimise the as proposed synthesis conditions of hollow Fe2O3 nanoparticles. While hollow Fe2O3 nanoparticles were not successfully synthesised, the work done could facilitate future work for optimisation of hollow Fe2O3 nanoparticle synthesis.